Efisiensi Waktu Change Model Injection Molding Machine Menggunakan Metode Single Minute Exchange Of Dies (SMED) di PT. XYZ - Muhammad Ali Yafi Yafi; Susan Kustiwan; Tri Ngudi Wiyatno (G-Tech: Jurnal Teknologi Terapan, 2024)
This study aims to improve the efficiency of the change model process in injection molding machines at PT. XYZ by applying the Single Minute Exchange of Die (SMED) method. Collected data includes process times, workstation layout configurations, and the effects of changes before and after SMED implementation. The research focuses on the injection molding line that produces components with different molds, requiring significant time for mold changes. Analysis identified 27 work elements in the change model process, aiming to reduce inefficiencies caused by manpower, material, environment, and methods. Improvements were made through training, work method standardization, and layout optimization. The implementation results showed a reduction in change model time by 17.6 minutes per session, increasing productivity and cost efficiency by Rp 1,692,810,- per month. Standardization and training also enhanced the safety and comfort of operators.